(untitled) (Research, Society and Development, 2020)
Objective: to evaluate musculoskeletal symptoms and behavior of biomarkers in public high school teachers in Caxias - MA. Methodology: The research was carried out at Inácio Passarinho Teaching Center and Aluízio de Azevedo Teaching Center. The study included all effective and classroom teachers during the data collection period. Data collection was performed by applying a socioeconomic questionnaire and peripheral blood collection to evaluate muscle markers. Results: the results that point teachers as a risk group for musculoskeletal problems, the quality of life impairments of these teachers not only reflect on the personal life of these workers, but also directly influence the teaching of students. Conclusion: these teachers are in a favorable condition for the onset of Repetitive Strain Injury (RSI) and Work-Related Musculoskeletal Disorders (WRMSD) and most of them presented physical and mental distress.